CYTOTOXICITY MEDIATED BY SOLUBLE ANTIGEN AND LYMPHOCYTES IN DELAYED HYPERSENSITIVITY : II. CORRELATION OF THE IN VITRO RESPONSE WITH SKIN REACTIVITY. - Ruddle, Nancy H. (The Rockefeller University Press, 1968)
Damage of rat embryo fibroblasts in the presence of sensitized lymph node cells reacting with specific antigen was shown to be closely correlated with delayed hypersensitivity in the animals from which the lymph node cells were taken. The phenomenon was not correlated with Arthus reactivity. In. animals sensitized with picryl conjugates of ovalbumin or human serum albumin, skin reactivity and the in vitro cytotoxic effect could be elicited only with the homologous conjugate or the protein carrier alone and not with picryl conjugates of heterologous proteins. Lewis rats developed more intense delayed sensitivity than BN rats, and Lewis lymph node cells were correspondingly more effective in producing specific damage of both syngeneic and allogeneic fibroblasts.